2017
DOI: 10.5796/electrochemistry.85.784
|View full text |Cite
|
Sign up to set email alerts
|

Sensing the Instant Corrosivity of Haze Using Electrochemical Probes by Electrochemical Noise Technique

Abstract: Electrochemical noise (EN) was used to study the corrosivity of haze under Tianjin's urban atmosphere by using two electrochemical corrosion probes made by T91 and Q235B steels. Experimental results indicate that temperature, relative humidity and concentrations of pollutants (PM10, PM2.5, SO 2 , NO 2 and O 3 ) can affect the corrosion of T91 and Q235B atmospheric corrosion monitoring probes. However, the atmospheric humidity has a major effect on corrosion activities. The corrosivity of haze under low tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…All electrochemical tests are measured in Faradi cage. The reference electrode (RE), working electrode (WE) and counter electrode (CE) were all used Q235 steel samples (MA et al , 2017; Arellano-Pérez et al , 2019). The frequency was set to 2 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…All electrochemical tests are measured in Faradi cage. The reference electrode (RE), working electrode (WE) and counter electrode (CE) were all used Q235 steel samples (MA et al , 2017; Arellano-Pérez et al , 2019). The frequency was set to 2 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Ma et al [ 72 ] also used EN to analyze the corrosion of haze under the atmosphere of urban Tianjin by using two electrochemical corrosion probes made by Q235B and T91 steels. Experimental results indicated that relative humidity, temperature and concentrations of contaminants could affect the corrosion of Q235B and T91.…”
Section: Electrochemical Corrosion Monitoring Of Various Substratementioning
confidence: 99%